Enhanced Fluorescence Properties of Stilbene‐Containing Alternating Copolymers. Issue 4 (6th December 2017) - Huang, Jing; Geng, Xi; Peng, Chong; Grove, Tijana Z.; Turner, S. Richard
Abstract: In recent years, nonconjugated, fluorophore‐free organic polymers have emerged as potentially useful light‐emitting materials. The fluorescence properties of a novel class of nonconjugated, tert ‐butyl carboxylate functionalized stilbene‐containing alternating copolymers are investigated in this work. These sterically crowded, semi‐rigid copolymers exhibit very strong blue fluorescence in organic solvents upon irradiation. The origin of the fluorescent band with high quantum yield is attributed to the "through space" π–π interactions between the phenyl rings from the stilbene and CO groups from the anhydride groups. To the best of our knowledge, the di‐ tert ‐butyl group‐containing stilbene and maleic anhydride alternating copolymer showed one of the highest fluorescent intensities among all fluorophore‐free polymers. The excellent linearity of the luminescence property of this copolymer is an important attribute for future potential quantitative applications. The fluorescence is maintained when the tert ‐butyl groups are removed and the resulting carboxylic acid‐functionalized copolymer is dissolved in water at neutral pH, which can render these copolymers as attractive candidates for diagnostic and therapeutic applications. Abstract : Nonconjugated, tert ‐butyl carboxylate functionalized stilbene‐containing alternating copolymers exhibit strong fluorescence with excellent linearity. The origin of the fluorescence is attributed to the "through space" π–π interactions between the phenyl rings from the stilbene and CO groups from the anhydride. The fluorescence is maintained when the tert ‐butyl groups are removed and the resulting carboxylic‐acid‐functionalized copolymer is dissolved in water at neutral pH.